2022
DOI: 10.3390/ijms23073863
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Three Tandemly Located Flagellin Genes of Stenotrophomonas maltophilia

Abstract: Stenotrophomonas maltophilia is a motile, opportunistic pathogen. The flagellum, which is involved in swimming, swarming, adhesion, and biofilm formation, is considered a virulence factor for motile pathogens. Three flagellin genes, fliC1, fliC2, and fliC3, were identified from the sequenced S. maltophilia genome. FliC1, fliC2, and fliC3 formed an operon, and their encoding proteins shared 67–82% identity. Members of the fliC1C2C3 operon were deleted individually or in combination to generate single mutants, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…FlrA is another important master regulon that initiates flagellar gene expression in an RpoN-dependent manner, which is required for proper flagellation and includes the polar flagellar number and morphology related to bacterial motility [48]. Additionally, another study found that flagellin mutants or flrA-, flrB-, or flrC-silenced strains affect filament morphology and the swimming, adhesion, and biofilm formation ability for its pathogenesis in Stenotrophomonas maltophilia and Vibrio alginolyticus [49,50]. Hence, we investigated whether the transcriptional levels of these flagellar regulons were affected by hcp2.…”
Section: The Transcriptions Of Sigma Factors Rpon and Flia Controllin...mentioning
confidence: 99%
“…FlrA is another important master regulon that initiates flagellar gene expression in an RpoN-dependent manner, which is required for proper flagellation and includes the polar flagellar number and morphology related to bacterial motility [48]. Additionally, another study found that flagellin mutants or flrA-, flrB-, or flrC-silenced strains affect filament morphology and the swimming, adhesion, and biofilm formation ability for its pathogenesis in Stenotrophomonas maltophilia and Vibrio alginolyticus [49,50]. Hence, we investigated whether the transcriptional levels of these flagellar regulons were affected by hcp2.…”
Section: The Transcriptions Of Sigma Factors Rpon and Flia Controllin...mentioning
confidence: 99%